2015
DOI: 10.1109/tps.2015.2433928
|View full text |Cite
|
Sign up to set email alerts
|

Electron Properties in Collisionless Mesothermal Plasma Expansion: Fully Kinetic Simulations

Abstract: This paper presents a fully kinetic particle-in-cell simulation of collisionless mesothermal plasma expansion with a focus on the macroscopic electron properties. The results show that the electron thermal properties are anisotropic and nonuniform. In the beam core region, the electrons are thermalized due to interactions between the trapped electrons and the potential well between the beam exit and the beam front. The electron expansion inside the beam is equilibrium and significant cooling occurs associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…The polytropic exponent γ e in the equation describes the exchange of heat between a magnetically expanding plasma and the system, and various kinetic modeling approaches have been established to explore the physical meaning of MN devices by relating the thermodynamic model to the MN phenomena, e.g. plasma detachment, plume divergence efficiency, and thruster gain [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The polytropic exponent γ e in the equation describes the exchange of heat between a magnetically expanding plasma and the system, and various kinetic modeling approaches have been established to explore the physical meaning of MN devices by relating the thermodynamic model to the MN phenomena, e.g. plasma detachment, plume divergence efficiency, and thruster gain [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The most common electron fluid model is the Boltzmann relation (BR). In the BR model it is assumed that the electrons are isothermal, the pressure is described by an ideal gas and the electron drift velocity can be neglected [11,12].…”
Section: Theorymentioning
confidence: 99%
“…Mora and Pellat () examined the use of equation for electrons in the derivation of the self‐similar solution of collisionless plasma expansion into a vacuum and found that the exact electron density differs from that predicted based on equation . Hu and Wang (, , ) carried out full particle PIC simulations of the emission and expansion of plasma plumes and found that the electron temperature is anisotropic and the electron velocity distribution function (VDF) is non‐Maxwellian in most of the plume region.…”
Section: Introductionmentioning
confidence: 99%